Folian-cv1 Is a Member of a Highly Acidic Phosphoprotein Class Derived From the Foliated Layer of the Eastern Oyster (Crassostrea virginica) Shell and Identified in Hemocytes and Mantle - Johnstone, Mary Beth; Wheeler, A. P.; Falwell, Elizabeth P.; Staton, Meg E.; Saski, Christopher A.; Mount, Andrew S. (Frontiers in Marine Science, 2019)
The proteins derived from the foliated layer of the oyster, Crassostrea virginica, shell are unusually acidic and highly phosphorylated, which together may be characteristic of molluscan shell having foliated microstructure. Here we report the identification of a gene encoding a member of this class of phosphoproteins that we collectively refer to as folian. Using an in silico approach, a virtual probe was constructed from a 7 amino acid N-terminal sequence (DEADAGD) determined for a 48 kDa folian phosphoprotein and used to screen an oyster EST databank. A sequence that matched the N-terminus of the 48 kDa protein was found and used to identify the full gene from a C. virginica BAC library. We named the gene folian-cv1 based on the shell layer and species of origin. The molecular weight of the deduced gene product, minus the signal peptide and putative phosphorylation and glycosylation, is 32 kDa. Genomic Southern analysis reveals two variants of the gene in the population studied that differ by 4 point mutations. The mature protein is composed of 43.3% Asp, 32.6% Ser and 9.1% Glu with 37.5% of the amino acids of the protein potentially phosphorylated. The primary sequence of folian-cv1 is organized in blocks, with a short relatively hydrophobic block at the N-terminus and with the remainder containing low complexity regions largely dominated by aspartic acid and serine arranged in various sequence patterns. Overall, the protein is predicted to be highly disordered. PCR and sequence analyses identified folian-cv1 expression in the mantle and hemocytes. Immuno-histochemical staining of mantle tissue reveals that cells of the shell-facing epithelium and in the periostracal groove secrete a continuous layer of folian-positive material and that folian-positive hemocytes move through the mantle epithelium. The function in shell formation of folian proteins in general and folian-cv1 in particular is not known. However, based on the complexity of this class of proteins and the two methods of their delivery to the region of shell formation, it is possible they are involved in diverse ways in this process.